An update on the performance of STI services for gay and bisexual men across European cities: results from the 2017 European MSM Internet Survey. Issue 3 (3rd November 2020) - Doran, Jason; Weatherburn, Peter; Hickson, Ford; Marcus, Ulrich; Reid, David; Schmidt, Axel Jeremias
Abstract : Objectives: Rectal STIs compromise health and are common in men who have sex with men (MSM). However, the European-MSM-Internet-Survey (EMIS-2010) showed that in 2010, the prevalence of anal swabbing during STI screening by MSM varied widely across 40 European cities. In this paper, we replicate a variety of measures of STI testing performance using 2017–18 data and extending the geographic spread of the analysis. Methods: Data were analysed from the EMIS-2017, a 33-language online sexual health survey accessible from 18 October 2017 to 31 January 2018. We focus on a subsample of 38 439 respondents living in the same 40 European cities we reported on in 2010. For a broader perspective, we also included an additional 65 cities in the analysis (combined n=56 661). We compared the prevalence of STI screening in MSM and disclosure of same-sex sexual contacts to the healthcare provider. We applied multivariable logistic regression models to compare the odds of MSM receiving each of four diagnostic procedures, including anal swabbing in the previous 12 months, controlling for age, HIV diagnosis, pre-exposure prophylaxis use and number of sexual partners. Results: In 2017, across 40 European cities, the proportion of respondents screened for STIs ranged from under 19% in Belgrade to over 59% in London. At an individual level, in comparison to London, the adjusted OR (AOR) of having received anal swabbing ranged from 0.03 in Belgrade, Bucharest and Istanbul to 0.80 in Oslo, with little evidence for a difference in Amsterdam and Dublin. Since 2010, most cities in West and South-west Europe have substantially narrowed their performance gap with London, but some in East and South-east Europe have seen the gap increase. Conclusions: Although comprehensive STI screening in MSM has expanded across many European cities, the low prevalence of anal swabbing indicates that rectal STIs continue to be underdiagnosed, particularly in East/South-east Europe.